Dimorphic histopathology of long-standing childhood-onset diabetes - Gianani, R; Campbell-Thompson, M; Sarkar, S. A; Wasserfall, C; Pugliese, A; Solis, J. M; Kent, S. C; Hering, B. J; West, E; Steck, A; Bonner-Weir, S; Atkinson, M. A; et al. (Diabetologia, 2010)
Aims/hypothesis Childhood diabetes is thought to usually result from autoimmune beta cell destruction (type 1A) with eventual total loss of beta cells. Analysis of C-peptide in children characterised at diabetes onset for autoantibodies shows heterogeneous preservation of insulin secretion in long-standing diabetes. The aim of this study was to characterise the pancreases of childhood-onset diabetes in order to define the pathological basis of this heterogeneity. Methods We evaluated 20 cadaveric organ donor pancreases of childhood-onset long-term patients for disease heterogeneity and obtained corresponding C-peptide measurements. Results Pancreases from the majority of cadaveric donors contained only insulin-deficient islets (14 of 20). The remaining six patients (30%) had numerous insulin-positive cells within at least some islets, with two different histological patterns. Pattern A (which we would associate with type 1A diabetes) had lobular retention of areas with ‘abnormal' beta cells producing the apoptosis inhibitor survivin and HLA class I. In pattern B, 100% of all islets contained normal-appearing but quantitatively reduced beta cells without survivin or HLA class I. Conclusions/interpretation Our data demonstrate that C-peptide secretion in long-standing diabetic patients can be explained by two different patterns of beta cell survival, possibly reflecting different subsets of type 1 diabetes.